If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -15x = 25 + 10x Solving 12 + -15x = 25 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + -15x + -10x = 25 + 10x + -10x Combine like terms: -15x + -10x = -25x 12 + -25x = 25 + 10x + -10x Combine like terms: 10x + -10x = 0 12 + -25x = 25 + 0 12 + -25x = 25 Add '-12' to each side of the equation. 12 + -12 + -25x = 25 + -12 Combine like terms: 12 + -12 = 0 0 + -25x = 25 + -12 -25x = 25 + -12 Combine like terms: 25 + -12 = 13 -25x = 13 Divide each side by '-25'. x = -0.52 Simplifying x = -0.52
| 0.05x+0.07(10000-x)=0 | | 8x^2=2/5 | | .21(10000)-.02y=.08(y+10000) | | 7x+10x-3= | | 10/x=5/30 | | 5x*3y=6 | | In11/13 | | t^2-3t=6 | | 8/5a-6/15 | | 21-2x=15 | | 3+11=2+-4 | | X/29=8.610 | | Y=2w*w | | 2lnx+ln(3)=0 | | -27/18x=1/2 | | 5+-10=3+-5 | | 6r-4r+3=9r+3-r | | w^2+8+15=0 | | cd+e=21 | | 3*5z^2+6= | | [16-52]/2= | | 4+1=4+7 | | g(-x)=3x^2-2x+12 | | 12r-bs=t | | 9=(n/3) | | 2a^2-6a-8=0 | | (14z^2+2)+(3z-4)=0 | | 6*4-2*5+(-21)= | | -3(5+3n)+6=-63 | | 4w+13x-7y=420z | | 5-2a-a=14 | | 3(2y+2)=-39 |